Requirement Model for Web Based Customer Ordering System - Segar Mart as Case Study - Geblawi, Bashir M. Mohamed (2006)
The major concern among the farmers these days are on distributing their products to the right customers at the right time. These farmers have been depending on "middle-person" to take their products to customers, This situation has restricted farmers to be more successful in selling their products and earn better profits. In today's digital economy, selling goods have moved from the traditional way to the new way of doing business on the Web. Seeing this as an opportunity, agricultural goods should not be excluded from this golden opportunity. This research project is intended to propose a requirement model for web-based customer ordering system. Requirement model provides a more structured and integrated guide fix the development of the system and serves is a good starting point for system development to understand users' requirement. To accomplish this research project, a case study has been conducted at Segar Mart which is a shop initiated by MOA for the farmers to sell their products direct to the customers. The requirements captured from the study are modelled out using Unified Modeling Language's (UML) notation. The prototype technique is used to validate the requirements. In this technique, a simple prototype is developed by using ASP as programming language, My SQL, Database server and Macromedia Dreamweaver for interfaces.